THE EFFECT OF PRODUCT INNOVATION AND DISCOUNTS ON BUYING DECISIONS FOR MSMES MEATBALLS IN MEDAN CITY DURING THE COVID-19 PANDEMIC - Bunga Aditi; Pasaman Silaban; Yusuf Ronny Edward (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Study this aim to find out how the Effect of Product Innovation and Discounts on Purchase Decisions for MSMEs Meatballs in Medan City During the Covid-19 Pandemic Period . Method research used _ is qualitative data method and quantitative data f. While the data used are primary and secondary data . Method data analysis in research _ this use multiple linear regression analysis . As for the results of this study, the first hypothesis D can be seen that the first hypothesis is rejected, it means that the innovation variable (X1) has no effect on the Purchase Decision (Y) variable . D it can be seen that the second hypothesis is accepted, meaning that the Discount variable (X2) has an effect on the Purchase Decision variable (Y). D it can be seen that the third hypothesis is accepted, meaning that the Innovation Variable (X1) and Discount Variable (X2) have a significant effect simultaneously (simultaneously) on the Purchase Decision Variable (Y).